Anti-Cancer Effects of 3, 3’-Diindolylmethane on Human Hepatocellular Carcinoma Cells Is Enhanced by Calcium Ionophore: The Role of Cytosolic Ca2+ and p38 MAPK - Jiang, Yuanyue; Fang, Yanfei; Ye, Yang; Xu, Xinming; Wang, Bingfang; Gu, Jie; Aschner, Michael; Chen, Jian; Lu, Rongzhu (Frontiers in Pharmacology, 2019)
Purpose: 3,3′-Diindolylmethane(DIM), derived from indole-3-carbinol (I3C) in the Brassica species of cruciferous vegetables, has anticancer effects, but its exact underlying mechanism of action remains unclear. We explored the roles of cytosolic free calcium ([Ca2+]i) and p38 MAPK in the anti-cancer effects of DIM in human hepatocellular carcinoma cells. Methods: Cell proliferation was measured with a Cell Counting Kit-8(CCK-8) and the clonogenic formation assay. Cell apoptosis was examined by flow cytometric analysis and Hoechst dye staining. Cleaved-caspase3, cleaved-PARP, Bax, total and phosphorylated p38MAPK were assayed by western blotting. [Ca2+]i was measured with Fluo-3/AM by fluorescence microscopy. A23187, a calcium ionophore, was used to increase [Ca2+]i levels. Results: DIM inhibited cell proliferation in both SMMC-7721 and HepG2 cells in a concentration- and time-dependent manner. DIM also enhanced phosphorylation of p38 MAPK(p-p38), which was attenuated by SB203580 and the proliferation inhibition and apoptosis induction by DIM were also blunted. In addition, DIM increased [Ca2+]i in hepatocellular carcinoma cells, and this effects was inhibited by the calcium chelator, BAPTA/AM, resulting in reduced p-p38 MAPK activation and apoptosis in DIM-treated cells, though the proliferation inhibition by DIM was unchanged. However, The DIM-induced cell proliferation inhibition and apoptosis were significantly enhanced by A23187, a selective calcium ionophore, which was attributed to exaggerated p-p38 MAPK. Conclusions: Calcium ionophore enhanced DIM-induced anti-cancer effects in hepatocellular carcinoma cells, secondary to [Ca2+]i-dependent activation of p38 MAPK. Treatment with a combination of DIM and calcium ionophore may offer a new approach to enhance the chemotherapeutic efficacy in liver cancer.